2021
DOI: 10.1002/ejic.202100371
|View full text |Cite
|
Sign up to set email alerts
|

Half‐Sandwich Nickel(II) NHC‐Picolyl Complexes as Catalysts for the Hydrosilylation of Carbonyl Compounds: Evidence for NHC‐Nickel Nanoparticles under Harsh Reaction Conditions

Abstract: The cationic [NiCp(Mes‐NHC‐CH2py]Br complex 2 a was prepared directly by the reaction of nickelocene with 1‐(2‐picolyl)‐3‐mesityl‐imidazolium bromide (1), and its PF6− derivative 2 b, by subsequent salt metathesis. X‐ray diffraction studies and Variable Temperature 1H NMR experiments run with 2 a and 2 b strongly suggest the bidentate coordination of the picolyl‐functionalized carbene to the nickel both in the solid state and in solution in both cases. These data suggest the absence of hemilabile behavior of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 95 publications
0
15
0
Order By: Relevance
“…High Ni contents in the collected precipitates were clearly established (Figures S87 and S88). It should be noted that the formation of Ni NPs is unsurprising because such precedents are known for reactions involving Ni(0) species in catalytic processes [14b,27] . On the one hand, metal NPs can represent a catalyst decomposition product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High Ni contents in the collected precipitates were clearly established (Figures S87 and S88). It should be noted that the formation of Ni NPs is unsurprising because such precedents are known for reactions involving Ni(0) species in catalytic processes [14b,27] . On the one hand, metal NPs can represent a catalyst decomposition product.…”
Section: Resultsmentioning
confidence: 99%
“…[14b,27] On the one hand, metal NPs can represent a catalyst decomposition product. On the other hand, the participation of NHCligated Ni NPs in catalysis as alternative active centers [27][28] or Ni NPs as metal reservoirs [29] should not be completely excluded.…”
Section: Chemcatchemmentioning
confidence: 99%
“…Furthermore, the persistence of the absorbance at 439 nm even after the addition of the oxidant ruled out possible hydrolysis of the imine functionality or hemilability of the N-Ni bond during the catalytic cycle [ 52 ]. However, the inactivation of the catalyst beyond 6 h might be due to possible catalyst degradation as observed in similar imine-containing complex catalysts [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in a recent report, we have shown that a half-sandwich Ni( ii )-NHC-picolyl bromide complex effectively catalysed the hydrosilylation of a broad range of aldehydes without additive and of ketones in the presence of KO t Bu at 100 °C. 9 Dynamic light scattering, scanning electron microscopy in transmission mode and X-ray photoelectron spectroscopy showed evidence of the involvement of NHC-picolyl Ni particles under the catalytic conditions used for the ketones’ reductions.…”
mentioning
confidence: 99%
“…7 To the best of our knowledge, there are only three reports on the use of NHC ligands to stabilise Ni NPs. 8,9 In the first two ones, such NHC-Ni NPs proved to be highly active catalysts for Kumada couplings 8a and the semi-hydrogenation of alkynes 8b and could be recycled a few times without significant loss of activity. Furthermore, in a recent report, we have shown that a half-sandwich Ni(II)-NHC-picolyl bromide complex effectively catalysed the hydrosilylation of a broad range of aldehydes without additive and of ketones in the presence of KOtBu at 100 °C.…”
mentioning
confidence: 99%